2007
DOI: 10.1007/s11434-007-0041-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent accumulation rate at Dome A, Antarctica

Abstract: Based on the horizon of β activity and the density profiles, recent accumulation rate at Dome A, Antarctica is calculated to be 0.023 m water equivalent per year. This value is comparative to the accumulation rates deduced from the other inland sites of Antarctica. Clear-sky precipitation (or diamond dust) dominates the total precipitation at Dome A region. We speculate Dome A as a potential site to discover the oldest ice in Antarctica due to its tremendous ice thickness (>3000 m), extremely low accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 11 publications
10
67
0
Order By: Relevance
“…Hence the net accumulation rate averaged over the two years was less than 0.016 cm water equivalent per year. The result is consistent with the estimation using nuclear test layer [18] and the modeling [25,26] . The accumulation rate at Dome A is approximately one third or half of the sites such as Vostok, Dome B and Dome F, or it roughly equals the averaged accumulation rate at Vostok during the last glacial maximum (LGM) period [7] .…”
Section: Geographysupporting
confidence: 88%
“…Hence the net accumulation rate averaged over the two years was less than 0.016 cm water equivalent per year. The result is consistent with the estimation using nuclear test layer [18] and the modeling [25,26] . The accumulation rate at Dome A is approximately one third or half of the sites such as Vostok, Dome B and Dome F, or it roughly equals the averaged accumulation rate at Vostok during the last glacial maximum (LGM) period [7] .…”
Section: Geographysupporting
confidence: 88%
“…1). Preliminary investigation has shown that the annual mean temperature (measured at 10 m below the surface) at Dome A is −58.5 • C, the lowest annual mean temperature ever recorded on the surface of the earth (Hou et al, 2007). The average snow accumulation rate during the past several centuries (AD 1260(AD -2004) is about 25 mm ice equivalent yr −1 (Jiang et al, 2012), which is typical of other sites in the East Antarctic interior (e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Consequently, seeking such kind of old ice cores from Antarctica is of vital importance, which is also one of the primary goals of the International partnership Ice Core Sciences (IPICS). Dome A, the highest point of the Antarctic ice sheet, is characterized by the lowest annual average temperature (58°C) [97], low accumulation rates (<25 mm/a water equivalent) [98,99], neglectable ice flow velocity and exceeding 3000 m ice thickness [100], meets the necessary conditions for retrieving such very old ice cores [101].…”
Section: Temperature Change At Orbital Timescalementioning
confidence: 99%